EFEKTIVITAS MODEL PEMBELAJARAN TREFFINGER GUNA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMPN 3 JOMBANG: THE EFFECTIVENESS OF THE TREFFINGER LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN CLASS VIII IPS LESSONS AT SMPN 3 JOMBANG - Mufarikha, Laili Asya (Jurnal Dialektika Pendidikan IPS, 2022)
The birth of the 2013 Curriculum to answer various educational challenges that are currently being faced. Implementation of the curriculum in education through an approach to students, so that students are expected to have great expertise, insight, and knowledge, so as to increase creative, innovative, and critical thinking. In order to help answer various challenges in the world of education, one of the efforts made is to provide innovative learning for students, one of which is a good learning model. The purpose of the study was to determine the effectiveness of Treffinger in order to improve student learning outcomes in Social Studies subject for class VIII at SMPN 3 Jombang. This type of research is quantitative with a quasi-experimental method (quasi-experimental) using a non-equivalent control group design. This study uses data collection techniques in research using Tests and Documentation. The sampling technique used was purposive sampling. data were analyzed using the SPSS Windows Version 21 The results of the research prove that the Treffinger effective in improving student learning outcomes with the percentage results of pretest, posttest and N-Gain results. The pretest 51.59 for the pretest were 52.25. And the results of the posttest 86.94 and the control class 73.56. while for the N-Gain the experimental class is 0.73% and the control class is 0.44%. Based on the research and discussion, it can be concluded that the Treffinger effectively implemented in learning in order to improve the learning outcomes of class VIII students in social studies subjects at SMPN 3 Jombang.